Дослідження ринку вагонобудування України та конкурентоспроможності промислових підприємств залізничного транспорту на світовому ринку та ринку країн СНД - Посохов, Ігор Михайлович (НТУ "ХПІ", 2015)
Виконано дослідження ринку вагонобудування України та конкурентоспроможності промислових підприємств залізничного транспорту на світовому ринку та ринку країн СНД. Запропоновано заходи зі зниження загроз політичної i економічної нестабільності країни, розроблено рекомендації з підвищення конкурентоспроможності промислових підприємств залізничного транспорту та напрями стратегії розвитку галузі вагонобудування на світовому ринку та ринку країн СНД.

The studies railcar market of Ukraine and the industrial competitiveness of rail transport on the global market and the CIS countries. The measures to reduce the threats to political and economic instability of the country, developed recommendations to improve the competitiveness of the industrial enterprises of railway transport development strategy and the direction of railcar industry in the global market and the CIS countries. In 2015, the vast number of car-building industry is in a difficult financial and economic situation, due to reduced demand and falling production volumes, was forced to develop crisis response operation of enterprises and the preservation of the industrial potential of the region.
Market research Ukraine railcar and industrial competitiveness of rail transport on the global market and CIS markets
Keywords: машинобудування; ринок збуту; продукція; Митний союз